Effect of Foreign Direct Investment on Energy consumption: Does Institutional Quality matter? Evidence from Cote d’Ivoire - Gakpa, Lewis-Landry; Kouadio, Hugues Kouassi (International Journal of Energy Economics and Policy, 2022)
This paper examines the role played by institutional quality in the relationship between foreign direct investment and energy consumption in CÃ´te d’Ivoire. Using data from the World Bank and International Country Risk Guid over the period 1984-2014 and the Dynamic Ordinary Least Squares (DOLS) and Fully Modified Ordinary Least Squares (FMOLS) methods, we account for the joint effects of institutional quality and foreign direct investment on energy consumption. The results reveal that a high level of democracy attenuates the negative effects of FDI flows on energy consumption. This result shows that improving and strengthening democratic institutions has a positive influence on energy efficiency incentive policies by changing the composition of FDI towards clean technology sectors, such as the service sector.